Аналіз фітонцидної активності деяких видів роду Ficus L. - Kharitonova, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Phytoncidous activity of 6 species from Ficus L. genus has been studied. All the tested plants showed certain phytoncidous impact on test-culture of pathogenic microorganisms that had been studied. The results show very high phytoncidous activity of Ficus pumile plants.